Increased expression of major histocompatibility complex antigens on lymphocytes from aged mice. - Sidman, C L (1987)
Many studies have reported age-related changes in immune responses that could be due to alterations in lymphoid cell numbers or functions. Here we report the results of studies using immunofluorescent staining and in vitro assays of cellular function to compare the expression of cell surface antigens on lymphocytes from mice up to 2 years of age. No significant changes were observed in the frequencies of spleen cells bearing class I or class II major histocompatibility complex (MHC) antigens, surface immunoglobulin, or Thy-1, Ly-1, Ly-2, or L3T4 antigens. However, the densities (per cell) of both class I and class II MHC antigens were increased significantly on cells from aged as compared to young mice, whereas the densities of the other cell surface antigens studied were unchanged or slightly decreased. The increased levels of MHC antigen expression in old relative to young mice were shown to be functionally significant regarding immunological stimulation. These data suggest that T-cell clones silent in young individuals may be activated in comparable situations in older animals, leading to immunological alterations perhaps including increased autoreactivity.